Raspad SFRJ: paraliza, agonija, rat - Vladimir Petrović (Istorija 20. Veka, 2018)
This article scrutinizes the disintegration of the federal level of government of the SFRY and its role in transforming the Yugoslav crisis into an armed conflict. This was a culmination of a long process in which centrifugal tendencies overcame the integrative capacity of Yugoslavia. A deep economic and social crisis surged dramatically in the wake of the collapse of the League of Communists of Yugoslavia in January 1990. This crisis led to a paralysis of the federal level of government exactly at the time which called for radical transformation and adjustment to the global changes signaled by the fall of the Berlin Wall. The Yugoslav government (Federal Executive Council), led by Ante Marković, was spearheading such a reformist program, but it faced ever stronger opposition from the conservative leadership of the armed forces. The agenda of the military, meanwhile, prioritized the preservation of the system, even at the expense of the country’s modernization. The space for addressing the mounting problems on the federal level was thus narrowing, enabling constitutive republics to act out their conflicting political projects. Empowered additionally by elections, which were never held on the federal level, leaders of the most influential republics fostered irreconcilable visions: Slovenia under Milan Kučan was planning its independence, hence changing Yugoslav external borders. Serbia under Slobodan Milošević was plotting to redraw internal borders between the republics, and Croatia under Franjo Tuđman was aiming to do both. The realization of such disparate plans called for the instrumentalization or marginalization of the federal government. In early 1991, this process was set in motion. The growing autonomy of republican leadership resulted in divisions within the SFRY Presidency and its inability to act decisively during the period in which Serbia undermined the federal monetary system, Croatia imported arms from abroad, and Slovenia held an independence referendum. Unchecked by civilian authorities, armed forces were pushing the Presidency into action through systemic pressures, peaking with an aborted coup in mid-March. The Yugoslav Presidency was hence effectively sidetracked, whereas the political dialogue about the Yugoslav future was relegated to summits of republican leaderships. These summits, held in late March and throughout April, did not produce any tangible results, as their actors attempted to legitimize their own positions by avoiding responsibility for the impending collapse and angled to maximize their gains in its course. The remaining federal authorities, Yugoslav government, and the military did attempt to stall this process. However, they failed to coordinate, maneuvering instead to oust each other. These attempts were abandoned in early May, amidst a number of armed incidents. With an increasing number of fatalities, the chances for peaceful resolution of the Yugoslav crisis were dwindling. Yugoslav federal authorities were increasingly unable to influence the course of events. Paralysis of the federal institutions blocked any institutional path toward resolving political problems. As the country moved from collapse into war, the divided representatives of the federal government either abdicated in front of their republican leaderships, or acted in cross-purposes, opening the path to the last stage of the Yugoslav agony.